Precarpathian National Universityin the European Educational Environment - Tsependa, Ihor (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The article looks at the problem of the development of Vasyl Stefanyk Precarpathian National University and the Europeanization of its education policy. The ways to improve the efficiency of research, through participation in international grant projects in particular, are in the focus of this paper. The fact that the papers by the University’s scientists are published in various SCOPUS indexed journals is evidence of the high quality and impact of their research outputs. It is an important factor in improving the University’s academic performance; it has allowed Precarpathian National University to rise to the level of the leading higher education institutions of Ukraine. The University has significantly increased its participation in various joint Ukrainian–European research projects; distinguished European scientists are invited to make presentations at the international conferences and symposiums held by the University. An ambitious project of reconstructing the astronomy observatory on Pip Ivan, a peak in the Carpathians, is being carried out in cooperation with the University of Warsaw. The Precarpathian National University has successfully implemented the double degree programme; now its students can receive the degree from Precarpathian National University and a European university. There has been developed a comprehensive programme of further Europeanization of the University’s policies